The Use of Self-Inflating Hygroscopic Tissue Expanders to Facilitate Osteosarcoma Removal in a Massasauga Rattlesnake (Sistrurus catenatus) - Kate E. Archibald; Brigid Troan; Dustin Smith; Larry J. Minter (Case Reports in Veterinary Medicine)
A 0.34 kg adult female Massasauga rattlesnake (Sistrurus catenatus) was presented for evaluation of a subcutaneous mass affecting the ventral scales. The mass was diagnosed as a sarcoma via punch biopsy with no evidence of metastasis on diagnostic imaging. Surgical margins of 1-2 cm were planned to achieve complete excision of the neoplasm. A technique for tissue expansion was employed due to concerns regarding the ability to close the surgical site without excess tension or dehiscence. Two 27 mm diameter×5 mm hygroscopic self-inflating tissue expanders were placed subcutaneously under the lateral scales adjacent to the mass. Maximum skin expansion occurred over a four-week period, and no direct negative effects were noted. Excision of the primary mass was performed routinely five weeks after implant placement. Primary closure of the defect was achieved with minimal tension by incorporating the expanded skin. While the surgery was successful with no evidence of metastasis, the snake died of sepsis two weeks postoperatively. This is the first report of the use of self-inflating hygroscopic tissue expanders to help close a surgical defect in a reptile.